2020
DOI: 10.3389/fnut.2020.606171
|View full text |Cite
|
Sign up to set email alerts
|

Can the FUT2 Non-secretor Phenotype Associated With Gut Microbiota Increase the Children Susceptibility for Type 1 Diabetes? A Mini Review

Abstract: The global toll of type 1 diabetes (T1D) has steadily increased over the last decades. It is now widely acknowledged that T1D pathophysiology is more complex than expected. Indeed, a multifaceted interplay between genetic, metabolic, inflammatory and environmental factors exists that leads to heterogeneous clinical manifestations across individuals. Children with non-secretor phenotype and those affected by T1D share low abundance of bifidobacteria, low content of short-chain fatty acids, intestinal phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 105 publications
0
16
0
1
Order By: Relevance
“…e bound L-fucose is catabolized and metabolized by a series of fucose degrading enzymes, which can ① be used as energy for bacteria; ② be internalized into fucosylated capsular polysaccharides (components of the bacterial cell wall); ③ be used to regulate the expression of fucose operon genes; ④ be used as raw material for bacteria to produce short-chain fatty acids (SCFAs). In addition, epithelial cell fucosylation can provide colonization advantages for bacteria containing fucosidase such as Bacteroides, increase the number of beneficial intestinal flora, and promote colonization resistance against opportunistic pathogens [9,10]. Some other studies have also pointed out that the composition of adult gut microbiota is related to the secretion status determined by the FUT2 gene [23], and histoblood group antigens may be a crucial genetic factor affecting the microecology of the intestinal flora [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e bound L-fucose is catabolized and metabolized by a series of fucose degrading enzymes, which can ① be used as energy for bacteria; ② be internalized into fucosylated capsular polysaccharides (components of the bacterial cell wall); ③ be used to regulate the expression of fucose operon genes; ④ be used as raw material for bacteria to produce short-chain fatty acids (SCFAs). In addition, epithelial cell fucosylation can provide colonization advantages for bacteria containing fucosidase such as Bacteroides, increase the number of beneficial intestinal flora, and promote colonization resistance against opportunistic pathogens [9,10]. Some other studies have also pointed out that the composition of adult gut microbiota is related to the secretion status determined by the FUT2 gene [23], and histoblood group antigens may be a crucial genetic factor affecting the microecology of the intestinal flora [24].…”
Section: Discussionmentioning
confidence: 99%
“…She et al have examined paraffin-embedded intestinal specimens from participants and found that the NEC patients showed lower intestinal epithelial fucosylation levels than the control patients [8]. At the same time, studies have shown that fucosylation of intestinal epithelial cells participates in the maintenance of gut microbiota homeostasis, and it is also of great significance in the colonization of intestinal symbiotic bacteria [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The GO [64], PLA2G6 [65], RGS2 [66], GPS2 [67], SOX5 [68], GLUL (glutamate-ammonia ligase) [69], RYK (receptor like tyrosine kinase) [70], NFKBIA (NFKB inhibitor alpha) [71], LGR4 [102], ITGAL (integrin subunit alpha L) [103], CD27 [104], JAK3 [105], CCR5 [106], FCN1 [107], IL1RN [108], CX3CR1 [109], PDCD1 [110], TRPM2 [111], PLEK (pleckstrin) [112], CD101 [113], TNF (tumor necrosis factor) [114], CD48 [115], ALOX5 [116], TLR7 [117], CCL3 [118], C2 [119], TNFRSF1B [120], CCR2 [121], PLA2G7 [122], TH (tyrosine hydroxylase) [123], WNT7A [124], ADRB3 [125], GPBAR1 [126], SLC6A20 [127], FUT2 [128], ANK1 [129], NOS3 [130], APLNR (apelin receptor) [131], COMP (cartilage oligomeric matrix protein) [132], RETN (resistin) [133], NMU (neuromedin U) [134], S100B [135], IGFBP1 [136], COL1A1 [137], HBB (hemoglobin subunit beta) [138] and PLAC8 [139] genes plays important regulatory roles in diabetes mellitus. Various genes such as PDK4 [140], ALB (albumin) [141], EGR1 [142], RYR3 [48], CYP27B1 [143], GATA6 [144], NR4A3 [145], TET2…”
Section: Discussionmentioning
confidence: 99%
“…Non-secretors (about 20% of the population) are more susceptible to infection by some pathogens ( Escherichia coli , Neisseria meningitidis , Streptococcus pneumoniae , Haemophilus influenzae , Candida albicans ) and have aberrant gut microbiota, with a reduction of beneficial Bifidobacterium spp. The FUT2 non-secretor phenotype increases susceptibility to Crohn’s disease, ulcerative colitis, primary sclerosing cholangitis, celiac disease, psoriasis, Behçet’s disease, type 1 diabetes, and so on but at the same time protects against H. pylori , which requires fucosylated glycans in the gastric mucosa for adhesion[ 35 , 39 , 40 ].…”
Section: To the Editormentioning
confidence: 99%